Meaning making in romantic relationship conflict: a scale creation and theory application considering adult attachment - Najman, Natalie, author; Quirk, Kelley, advisor; Harvey, Ashley, committee member; Hastings, Pat, committee member (Colorado State University. Libraries, 2023)
While existing literature on conflict and attribution theory reveal valuable information about the relationship between cause of conflict and blame, a new theory of meaning making of relationship conflict may offer a focused lens to examine the ways couples make sense of an argument and provide a more complete assessment of conflict. The goals of the first study presented here were to establish the meaning making of relationship conflict theory (MORC) as a framework for understanding relationship-specific meaning making tendencies and introduce a new MORC scale. The MORC scale was hypothesized to identify three theoretically distinct categories of meaning making following relationship conflict: self-focused, partner-focused, and couple-focused. Results confirmed that people make meaning of relationship conflict by focusing on themselves, their partner, or their relationship more broadly. The second study aimed to establish MORC scale validity and explore adult attachment as a potential predictor of meaning making tendencies. Individuals (N = 214) were assessed using the Experiences in Close Relationship Scale (ECR-SF), Cognitive and Affective Mindfulness Scale (CAMS-R), Perseverative Thinking Questionnaire (PTQ), and the Meaning Making of Relationship Conflict Scale (MORC). Results found a significant, strong, positive correlation between rumination and the MORC scale and a significant, strong, negative correlation between mindfulness and the MORC scale. Next, results revealed support of attachment as a potential mechanism that influences meaning making. Individuals with greater insecure attachment styles (dismissive and anxious/preoccupied) reported higher scores for meaning making of conflict. Individuals with higher avoidant or anxious scores were found to be more likely partner-focused in their meaning making. Secure attachment was not found to be a predictor for meaning making of conflict.
Keywords: couples; MFT; meaning making; conflict